2010
DOI: 10.1111/j.1540-4609.2009.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Student Perceptions of Which Classroom Policies Are Fairest

Abstract: Fairness is a critical issue in the educational setting, and the research is unified in the view that professors need to be fair in setting course policies and procedures. However, many unanswered questions still remain as to which specific classroom policies and procedures students find fair or unfair. This study explores student perceptions of which course policies provide the fairest treatment for all students in a college class. In addition, we also investigate the presence of a relationship between studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…Their findings defied the established beliefs that perception of fairness is merely driven by perception of justice; rather, they demonstrated that charismatic qualities also predict the evaluation of fairness significantly. Similar findings have also been reported in the literature of classroom fairness in relation to the influence of learning styles(Crosthwaite, Bailey, & Meeker, 2015) and personality types(Duplaga & Astani, 2010) on students' perception of fairness. For example,Crosthwaite et al (2015) detected that students…”
supporting
confidence: 88%
“…Their findings defied the established beliefs that perception of fairness is merely driven by perception of justice; rather, they demonstrated that charismatic qualities also predict the evaluation of fairness significantly. Similar findings have also been reported in the literature of classroom fairness in relation to the influence of learning styles(Crosthwaite, Bailey, & Meeker, 2015) and personality types(Duplaga & Astani, 2010) on students' perception of fairness. For example,Crosthwaite et al (2015) detected that students…”
supporting
confidence: 88%
“…Similarly, 89 percent of students in a qualitative exploration on what classroom procedures they perceive (un)fair reported that homework collection schedule should be notified earlier (Duplaga & Astani, 2010).…”
Section: Procedural Justicementioning
confidence: 99%
“…Although we have described just one domain (e.g., grading) where each principles of procedural justice were applied, studies have demonstrated that students generally apply principles of procedural justice in domains such as attendance policy (Houston & Bettencourt, 1999), course work load (Horan et al, 2010;Rodabaugh, 1994;Whitley et al, 2000), make-up policies (Horan et al, 2010), missed work policies (Houston & Bettencourt, 1999), tests (Gordon & Fay, 2010;Houston & Bettencourt, 1999;Pepper & Pathak, 2008), feedback provision (Whitley et al, 2000), and sanctions for cheating on an exam (Duplaga & Astani, 2010). For example, Seevers, Rowe, and Skinner (2014) examined the transparency of feedback (i.e.…”
Section: Procedural Justicementioning
confidence: 99%
See 1 more Smart Citation
“…Across eight potential classroom situations using a sample of business undergraduates, Duplaga and Astani (2010) explored which classroom policy statement within each situation provided the fairest treatment for all students in class. The eight situations were: attendance, collection and grading of homework, extra credit, late assignments, make-up exams, make-up quizzes, sanctions imposed for cheating on a quiz, and sanctions imposed for cheating on an exam.…”
Section: Review Of the Literature-grading Fairness Assessmentmentioning
confidence: 99%